The unseen pandemic: treatment delays and loss to follow-up due to fear of COVID - Sharon Einav; James Tankel (Journal of Anesthesia, Analgesia and Critical Care, 2022)
Abstract Background Fear of contracting SARS-CoV-2 has transformed public interaction with healthcare professionals and hospitals alike. In turn, this has resulted in a collateral impact on patients’ health across medical and surgical paradigms. Understanding the causative factors of this fear, and tackling it head on, is vital to return to pre-pandemic levels of healthcare. Main body In this editorial, we explore the evidence base behind the fear of healthcare professionals and facilities that has developed during the course of the SARS-CoV-2pandemic. We also reflect on the ways in which these fears have affected the general public. In so doing, we review a recent article from Montalto et al. that has explored fear of SARS-CoV-2 among patients undergoing surgery in Italy. Conclusion While fear of SARS-CoV-2 is uncommon among surgical patients, there are still those who delay or avoiding seeking medical care due to fear of transmission. Physicians must lead the fight against this fear in a hope to regain the trust of the public.